Sustainability evaluation of cold-bonded aggregates made from waste materials. (10th November 2019) - Thomas, Job; Harilal, B.
Abstract: Cold-bonded aggregates are technically feasible alternatives to conventional crushed stone aggregates (CSA) in concrete production, but the sustainability of cold-bonded aggregates has not yet been studied. Therefore, this paper suggests a framework for evaluating the sustainability of cold-bonded aggregates. The three pillars of sustainability, namely, social, environmental and economic factors, were used as the main criteria in the evaluation process. Cold-bonded aggregates made from waste materials such as fly ash and quarry dust were used in this study. The sustainability indices of cold-bonded fly ash aggregate (CBFAA) and cold-bonded quarry dust aggregates (CBQDA) were determined and compared with that of CSA. Fourteen sub-criteria were identified for this study. Out of the 14 sub-criteria, six sub-criteria were identified as social factors, another six were identified as environmental factors and two were identified as economic aspect factors. OF the 14 sub-criteria, eleven sub-criteria were qualitative in nature and three were quantitative. A qualitative assessment was conducted via a questionnaire survey of 254 registered practicing engineers. A quantitative evaluation of the embodied energy, lifecycle cost (LCC) and capital cost was performed in this study. The multi-index comprehensive analysis model was used to compute the sustainability indices of different types of coarse aggregates. The sustainable indices of CSA, CBFAA and CBQDA were found to be 0.610, 0.737 and 0.789, respectively. This result indicates that cold-bonded aggregates are sustainable and can be considered for used concrete production. The sensitivity analysis results indicated that the amount of binder and distance to the source of raw materials are important aspects. The framework developed in this study can be used to evaluate other building materials that are relatively new in origin. Highlights: A framework for performing a sustainability evaluation of artificial aggregates was proposed. Fourteen sub-criteria were identified used the triple bottom method to perform a sustainability evaluation. The qualitative score assigned by the stakeholders was found to be favorable for cold-bonded aggregates. The sustainability index of cold-bonded aggregates was found to be greater than that of conventional crushed stone aggregates. The quantity of the binding constituent and the source distance on sustainability index are the sensitive factors.